Морфологічні особливості Bidens сonnata Muehl. ex Willd. у різних частинах вторинного ареалу (європейська частина Росії, Україна) - Galkina, M.A.; Makhinya, L.M.; Vinogradova, Yu.K.; Ryabchenko, A.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
A comparative analysis of morphological characte ristics of Bidens connata Muehl. ex Willd. in Russia (Kaluga and Kaliningrad regions) and in Ukraine (Kyiv and Poltava regions) are made. B. connata grows in ruderal habitats. This species settled in natural plant communities (meadows in alluvial lands). We found wide variability in morphological parameters of B. connata growing in different localities of the area.